Indian black rice: A brewing raw material with novel functionality. Issue 1 (3rd November 2019) - Moirangthem, Kamaljit; Jenkins, David; Ramakrishna, Priya; Rajkumari, Ranjana; Cook, David
Abstract: Indian black rice ( Chakhao Poireiton) is a pigmented variety, rich in anthocyanins and other phytonutrients. With growing interest in the use of local raw materials in brewing, it was of interest to develop protocols for malting and brewing with Chakhao Poireiton to see whether the antioxidant capacity of anthocyanins could be delivered into finished beer. Protocols for brewing with 100% malted rice were developed and the performance of Indian black rice compared with that of an Italian white rice cultivar suited to brewing. The apparent fermentabilities of rice worts were 69.5% (black) and 67.3% (white), yielding beers of 3.28 and 3.19% ABV respectively. Black rice worts were deficient in free amino nitrogen (83.5 mg/L relative to 137 mg/L for white rice) and would need nitrogen supplementation to avoid issues with fermentation, e.g. elevated diacetyl. Black rice beer had an orange‐red hue as a result of extraction of anthocyanin pigments (2.84 mg/L). The oxidative stability of 100% rice beers was measured using electron spin resonance spectroscopy and both samples were found to be unusually stable. Interestingly, when rice beers were blended with a control barley malt derived lager in varying proportions (10, 25, 50%), the oxidative stability was improved, relative to the control lager, particularly so in the case of black rice beer, which contained an antioxidant capacity over and above that of the white rice beer. Future studies are required to determine whether the noted oxidative stability of 100% rice malt beers results in a more flavour‐stable beer. © 2019 The Institute of Brewing & Distilling